(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the methodology for developing students’ independent learning competence in digital education. It analyzes the importance of digital tools, online learning platforms, and teacher facilitation in fostering autonomous learning. The paper emphasizes strategies such as blended learning, project-based learning, and personalized feedback systems. Through the integration of digital technologies, students can enhance critical thinking, problem-solving, and self-regulation skills necessary for lifelong learning in the modern digital society.